Bats in cobwebs of the giant-spider Nephilingis cruentata (Fabricius, 1775) (Araneae: Nephilidae) in Brazil - Fábio André Facco Jacomassa; Marcela Benavides Guzman; Matheus Dourado (Biotemas, 2015)
Bats throughout the world are preyed upon primarily by vertebrates, but some are also attacked by invertebrates. We report two cases of bats entangled in webs of the giant-spider Nephilingis cruentata in southeastern Brazil. The first incidence occurred in December 2012, on which a female Eptesicus diminutus was found dead. The second occurred in March 2013, in which a male Tadarida brasiliensis was removed from the web alive, and later released. The animals showed no predation marks on the body, and both events were recorded after heavy rains. We suspect that the bats may have become entangled in the webs while seeking shelter from rain, or while foraging for insects. Even though the bats were not preyed upon, this spider cannot be ruled out as an opportunistic predator of small bats, as has been observed outside of Brazil.